An Analysis of Legal Fairness in the Protection of Dividend Rights for Minority Shareholders in Limited Liability Companies - Hermanto; Suci Hati Handayani; Ingka Harsani Nasution (PT. Radja Intercontinental Publishing, 2026)
This article analyzes legal fairness in the protection of dividend rights for minority shareholders in limited liability companies. The issue is significant because dividend distribution represents a fundamental economic right of shareholders, yet minority shareholders often occupy a vulnerable position when corporate decisions are dominated by majority shareholders through the General Meeting of Shareholders. This study aims to examine whether existing legal norms and corporate governance principles provide fair and proportional protection for minority shareholders in dividend-related decisions. The research applies a normative juridical method with statutory and conceptual approaches. Data were collected through literature study and analysis of relevant laws, regulations, legal doctrines, and corporate governance principles; therefore, this study does not involve respondents or informants. The data were analyzed qualitatively through legal interpretation, conceptual analysis, and systematic reasoning. The findings indicate that legal protection for minority shareholders’ dividend rights remains largely formal and depends heavily on transparency, accountability, and good faith in corporate decision-making. Majority control may create potential unfairness when dividend policies are determined without sufficient consideration of minority shareholders’ legitimate economic interests. This study concludes that stronger substantive legal protection and fairer governance mechanisms are necessary to promote equitable dividend distribution and enhance corporate accountability.